2023
DOI: 10.1101/2023.02.24.529988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of Influenza virus andStreptococcus pneumoniaein air sampled from co-infected ferrets and analysis of their influence on pathogen stability

Abstract: Secondary infection withStreptococcus pneumoniaehas contributed significantly to morbidity and mortality during multiple influenza virus pandemics and remains a common threat today. During a concurrent infection, both pathogens can influence the transmission of each other, but the mechanisms behind this are unclear. In this study, condensation air sampling and cyclone bioaerosol sampling were performed using ferrets first infected with the 2009 H1N1 pandemic influenza virus (H1N1pdm09) and secondarily infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Specifically, airborne particles between 0.65 – 3.3 μm dry size were enriched for both pathogens when they were co-aerosolized, though it is possible that particles outside of the tested size range (i.e., < 0.65 μm) could also contain high levels of IAV. An animal study previously identified both S. pneumoniae and IAV within the same expelled aerosol fraction from co-infected ferrets (32), and it is promising that the mechanical system utilised in our study could reproduce these animal-based findings. Stabilisation of IAV by co-aerosolized bacteria was also observed in our data, with IAV retaining higher infectivity for at least 45 minutes in indoor air conditions (40% RH) when bacteria were also present in the inoculum ( Fig.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Specifically, airborne particles between 0.65 – 3.3 μm dry size were enriched for both pathogens when they were co-aerosolized, though it is possible that particles outside of the tested size range (i.e., < 0.65 μm) could also contain high levels of IAV. An animal study previously identified both S. pneumoniae and IAV within the same expelled aerosol fraction from co-infected ferrets (32), and it is promising that the mechanical system utilised in our study could reproduce these animal-based findings. Stabilisation of IAV by co-aerosolized bacteria was also observed in our data, with IAV retaining higher infectivity for at least 45 minutes in indoor air conditions (40% RH) when bacteria were also present in the inoculum ( Fig.…”
Section: Discussionmentioning
confidence: 55%
“…6B ) mediated by S. pneumoniae. An unrelated study investigating S. pneumoniae and IAV in small droplets of respiratory matrix conversely found that bacterial presence did not improve viral stability (32). However, this study used complex airway surface liquid collected from cultures of human lung bronchial epithelial cells, and in this fluid, IAV alone was suitably stable already (authors measured 1-log10 decay total over multiple hours).…”
Section: Discussionmentioning
confidence: 99%